Os efeitos do seguro garantia judicial e da fiança bancária em execuções fiscais: suspensão da exigibilidade e impossibilidade de protesto da cda e inclusão do contribuinte no CADIN - Benvenuti, Vitor Fantaguci (2021)
The main purpose of this paper is to analyze the main theoretical aspects related to the causes of suspension of tax liability and the process of positivation of legal rules, as well as to analyze three possible interpretative constructions to support the impossibility of protesting the debt and enrollment in the defaulters' registry based on credits secured by judicial guarantee and bank guarantee. This is a very relevant and current issue, since several taxpayers use the insurance guarantee and the bank guarantee as collateral in tax foreclosures, but face legal uncertainty due to diverging interpretations by the Judiciary on the effects of the attachment of these guarantees. In the end, we will verify that, depending on the premises adopted, there are at least three interpretative possibilities to reach the same conclusion: it is unfeasible to protest the debt and enroll the taxpayer in the defaulters' list based on tax credits secured by judicial guarantee or bank guarantee. In this way we can list the legal grounds that must be adopted by the court decisions dealing with the issue, considering the requirement of adequate grounds for the decisions